Spontaneous Consumption Coagulopathy in a Dog with Thyroid Cancer - Slappendel, R. J; de Maat, C.E.M; Rijnberk, A; van Arkel, Miss C (Thrombosis and Haemostasis, 1970)
A case of metastasized anaplastic thyroid carcinoma associated with severe hemorrhagic diathesis in a boxer dog is described. The bleeding tendency was apparently due to consumption coagulopathy, since there was simultaneous occurrence of thrombocytopenia, hypofibrinogenemia and depletion of clotting factors II, V, VIII and X. Fibrinogen breakdown products were demonstrated by three different immunochemical techniques.